ANALISIS PENERAPAN PERENCANAAN PAJAK PENGHASILAN PASAL 21 PADA PT JAYA MESTIKA INDONESIA - Indriati, Dewi; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTTax is one of the sources of state revenue that is very important. Tax is a compulsory contributions which is levied by the state on the contrary, tax is a burden for a company. In order to minimize the tax burden, the company can implement tax planning and one of the ways is by using Income Tax 21. This research is aimed to find out the role of the planning application that has been done by PT Jaya Mestika Indonesia and to compare the calculation of income tax 21 by using the net method and the gross-up method and the impact whihc has been generated by these two methods to the corporate income tax payable. This research uses primary and secondary data. The primary data has been obtained by performing interviews to the authorities within the company about the type of tax planning which has been implemented by the company and the secondary data is in the form of financial statements, employee payroll, and other supporting documents. The result of this research shows that the calculation of employee income tax 21 has been done by using the gross-up method can raise the salaries burden and reduce the taxable income so that it gives a small impact to the value of corporate income tax, this issue can be used as one of the efforts of the company to minimize income tax payable.Keywords: tax planning, income tax 21, gross up method.